1999
DOI: 10.1073/pnas.96.23.13097
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of SQD1, an enzyme involved in the biosynthesis of the plant sulfolipid headgroup donor UDP-sulfoquinovose

Abstract: The SQD1 enzyme is believed to be involved in the biosynthesis of the sulfoquinovosyl headgroup of plant sulfolipids, catalyzing the transfer of SO 3 ؊ to UDP-glucose. We have determined the structure of the complex of SQD1 from Arabidopsis thaliana with NAD ؉ and the putative substrate UDP-glucose at 1.6-Å resolution. Both bound ligands are completely buried within the binding cleft, along with an internal solvent cavity which is the likely binding site for the, as yet, unidentified sulfur-donor substrate. SQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
54
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 48 publications
5
54
0
Order By: Relevance
“…These two specific reactions have been determined to occur in chloroplasts based on feeding experiments of isolated chloroplasts with 35 S-labeled sulfate, which revealed that chloroplasts were fully capable of synthesizing SQDG from labeled sulfate (Haas et al, 1980;KleppingerSparace et al, 1985;Joyard et al, 1986;Mudd, 1987, 1990;Pugh et al, 1995) and based on enzyme activities of SQD1 and SQD2 in the chloroplasts (Heinz et al, 1989;Seifert and Heinz, 1992;Tietje and Heinz, 1998;Shimojima et al, 2005). Recombinant SQD1 proteins have been shown to have UDP-SQ synthase activity (Essigmann et al, 1998;Shimojima and Benning, 2003), and the crystal structure of the Arabidopsis SQD1 protein and detailed possible reaction mechanism have been reported (Mulichak et al, 1999;Essigmann et al, 1999). In addition, analysis of SQD1 purified from leaves of spinach (Spinacia oleracea) suggested that native SQD1 interacted with ferredoxin-dependent glutamate synthase to form a large protein complex in the stroma of plants (Shimojima et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…These two specific reactions have been determined to occur in chloroplasts based on feeding experiments of isolated chloroplasts with 35 S-labeled sulfate, which revealed that chloroplasts were fully capable of synthesizing SQDG from labeled sulfate (Haas et al, 1980;KleppingerSparace et al, 1985;Joyard et al, 1986;Mudd, 1987, 1990;Pugh et al, 1995) and based on enzyme activities of SQD1 and SQD2 in the chloroplasts (Heinz et al, 1989;Seifert and Heinz, 1992;Tietje and Heinz, 1998;Shimojima et al, 2005). Recombinant SQD1 proteins have been shown to have UDP-SQ synthase activity (Essigmann et al, 1998;Shimojima and Benning, 2003), and the crystal structure of the Arabidopsis SQD1 protein and detailed possible reaction mechanism have been reported (Mulichak et al, 1999;Essigmann et al, 1999). In addition, analysis of SQD1 purified from leaves of spinach (Spinacia oleracea) suggested that native SQD1 interacted with ferredoxin-dependent glutamate synthase to form a large protein complex in the stroma of plants (Shimojima et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…1), catalyzed by the SQD1 protein in Arabidopsis (8). The crystal structure for this protein is known, and a reaction mechanism has been proposed (9,10). On the contrary, although the activity of the sulfolipid synthase catalyzing the last step of sulfolipid biosynthesis has been fairly well characterized in spinach chloroplast extracts (11), the protein had not been isolated, and the respective gene remained unidentified.…”
mentioning
confidence: 99%
“…It was suggested that these proteins catalyze a reaction between UDP-glucose (UDP-Glc) and a suitable sulfur donor leading to the formation of UDP-SQ (5,14). The SQD1 protein of Arabidopsis thaliana is an orthologue of the bacterial SQDB proteins (15), and its crystal structure has been elucidated (16). Recombinant SQD1 lacking the chloroplast transit peptide has a mass of 45.5 kDa, forms a dimer, and contains a buried active site with tightly bound NAD ϩ (16,17).…”
mentioning
confidence: 99%